Integration of Science and Theology: Transformation of Religious Paradigm in National Disaster Mitigation Policy - Venny Rosalina (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
The integration of spiritual values and scientific data is crucial in facing the increasing frequency of natural disasters in Indonesia. Thus far, overly technocratic disaster management policies have often failed at the grassroots level due to ignoring the emotional and theological attachment of society to nature. The phenomenon of theological fatalism, where disasters are perceived as an absolute destiny that cannot be intervened, remains a major obstacle to human agency in taking preventive actions. This policy paper aims to formulate a transformation of religious paradigms through an ecotheological approach to eliminate the dichotomy between religious studies and disaster science. The policy methodology employed includes problem identification using the Urgency, Seriousness, and Growth (USG) method to determine handling priorities, alongside root cause analysis using a fishbone diagram. The analysis results indicate that theological fatalism is the most pressing issue, rooted in literal interpretations of texts and the limitations of hermeneutical methodology in traditional educational institutions. Based on scoring using William N. Dunn's criteria, the recommended policy alternatives include a Regulation of the Minister of Religious Affairs on Mainstreaming Ecotheology in the Religious Education Curriculum and the standardization of ecological competence for religious extension officers. The implementation of this policy is expected to reshape anthropocentric views into ecocentric ones, transforming passivity into responsive agency, and uniting reason and faith as the foundation of national resilience.